Observational Research On Urban Public Awareness of Ayurveda as an Adjuvant Therapy During COVID-19 : Life Sciences- Ayurveda - Riyaz Mirza, Shumaila; Sawarkar, Dr. Gaurav; Sawarkar, Dr. Punam (International Journal of Life Science and Pharma Research, 2023)
Ayurveda labels COVID-19 as Janapadodhwamsa Vikara (epidemic disease). Charaka Samhita: Vimana Sthana Chapter 3discusses epidemics; even though there is dissimilarity in the physical constitution of human beings; still there are such factorsthat are common to all individuals, and vitiation of these factors lead to the simultaneous manifestation of diseases having thesame set of symptoms leading to the destruction of countries. All citizens share air, water, location, and seasons. The subjectswere drawn from the general population who had tested positive for COVID-19. An accurate and comprehensive questionnairewas used to conduct the online survey. All of the responses were correctly completed. All information was gathered from theonline survey and properly analysed. This study included 250 COVID-19-positive participants. A questionnaire and verbaldialogue assessed COVID-19 ayurvedic adjuvant therapy utilization. 89.6% had COVID-19. 65.6% of patients have RTPCR toconfirm COVID-19. 81.2% of COVID-19 patients initially used allopathic medication, with 59.6% reporting negative effects. Afterthat, 87.2% received ayurvedic COVID-19 medicine. 96.4% of COVID-19 patients had a fever, cold, cough, and weakness.Mahasudarshana Kadha (71.2%), Samshavani Vati (66.4%), and Sitopaladi Churna (51.2%) were the top three COVID-19 medicines.Most nations treat COVID-19 with antiviral combinations for other viral infections. SARS-COV-2 antivirals may not workclinically. Ayurveda treats sickness via mind-body-physiology. Ayurvedic medicine boosts immunity and fights viruses. Ayurvedaadjuvant therapy helped COVID-19 patients. Ayurveda can treat COVID-19 symptoms without side effects.